Citizenship, democracy and belonging in suburban Britain : making the local - Jeevendrampillai, David (UCL Press, 2021)
Citizenship, Democracy and Belonging in Suburban Britain follows a group of community activists in suburban London, as they take on the responsibilities and pressures of being good citizens.